Website quality affects online complusive purchase behaviour of students faculty of economics and business UNP - Astuti, Kristiana; Sari, Nadhila; Batubara, Hani Maisyarah; Anwar, Kendis; Evanita, Susi; Dwita, Vidyarini (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Website quality can encourage consumers to purchase goods easily through an app. This in turn increases online shopping behaviour. Recently, there is a tendency that shoppers consider impulsive behaviour when making online purchases. The purpose of this study was to determine the Impact of Website Quality on Online Compulsive Purchasing Behaviour of UNP Faculty of Economics Students. This type of research uses quantitative survey methodology. Consumer demographics were randomly selected from a database of Instagram visits and followers. A total of 112 respondents, collected using the incidental sampling method, were sampled. A link to the survey was provided to collect data.The research instruments used in the study included online compulsive buying behavior measurement scale, website quality assessment tool, online impulsive buying behavior measurement scale, and demographic questionnaire.The SEM analysis technique method was used for data analysis. According to the research findings, website quality has an impact on the significance of compulsive behaviour mediated by impulsive buying behaviour online. The partial significance test shows the difference between the R-Square value of online impulsive buying of 56.3 percent including moderate influence. As well as the magnitude of the influence of website quality on impulsive buying of 64.4 percent including high influence.